Ayala Corp: Helping in rapid ramp-up of the Philippines test trace and treat (T3) - DEMEESTER, Lieven (Institutional Knowledge at Singapore Management University, 2024)
In 2023, Guillermo M. Luz, Associate Director at Ayala Corporation, reflected on the challenges of the COVID-19 pandemic in the Philippines, recalling both the sorrow of lost lives and the pride in Ayala’s role in saving others. Luz had played a crucial role in the national Task Force T3 (T3)—an innovative public-private partnership established by the Philippines government to combat the pandemic. The T3 initiative, which focused on testing, tracing, and treatment, had achieved many successes despite numerous hurdles. Looking back, Luz couldn't help but wonder if some of the compromises made along the way were truly necessary. For instance, Ayala had been instrumental in setting up several testing labs across the country to boost testing capacity, but despite its efforts, some of these labs had operated at only 35% capacity. Luz recognised that the unprecedented uncertainties of the COVID-19 crisis made compromises unavoidable. The T3 initiative demonstrated the critical role of coordination, stakeholder engagement, and resource sharing in executing national projects under challenging conditions. He wondered if these lessons could serve as a blueprint for managing future crises. This case can be used in undergraduate, postgraduate and executive education classes to discuss crisis management and project management under uncertainty. The case allows students to analyse the impact of uncertainty and assess risk management techniques, communication strategies, management strategies, and project outcomes. Additionally, students will be able to synthesise (a) how global crises like COVID-19 create uncertainties that affect project planning and execution (b) analyse the outcomes of projects managed under conditions of extreme uncertainty and suggest areas for improvement (c) Corporate Social Responsibility and the role of business in the social context (d) Public Private Partnerships (PPP) and strategies for successful PPP execution.